Status of crop raiding by Assamese monkeys (Macaca assamensis) along the Budhigandaki river, central Nepal - Ghimire, Suvas Chandra; Chalise, Mukesh Kumar (Journal of Natural History Museum, 2018)
Crop depredation study was done on Assamese monkeys (Macaca assamensis) in Budhigandaki river basin lying on Dhading and Gorkha districts of central Nepal. The field study was conducted from February 2015 to January 2016 spending 1804 hours to explore the ecology and feeding behavior of Assamese monkeys. The study mainly focused at Kallerivillage of Salang village development committee of Dhading district and Baseri, Majhitar and Siurenitar villages of Ghyalchok village development committee of Gorkha district. A total of16 individuals of Assamese monkeys were counted at Rigdi khola of Sigrepakha community forest of Salang village development committee of Dhading district whereas a total of 13individuals of Assamese monkeys were counted at Sandkhola of Benigam community forestand a total of 14 individuals of Assamese monkeys counted at Siurenitar of Ghyalchok village development committee of Gorkha district. Crop raiding data were collected by questionnaire survey method to local households in the nearby villages and also by direct observation. It was found that maize (58.43%) was the highest raided, followed by rice (11.34%), lentil(8.74%), peanut (4.35%), soyabean (4.18%), wheat (3.22%), fruits (2.97%), black pulses(1.87%), potato (1.67%), sesham (0.92%), tomato (0.79%), millet (0.67%), mustard (0.36%),broad beans (0.25%), brown lentil (0.18%) and pumpkin (0.06%).